"Maxed Out on Efficiency": Logger Perceptions of Financial Challenges Facing Timber Operations. (7th February 2022) - Rissman, Adena R.; Geisler, Ellen; Gorby, Tricia; Rickenbach, Mark G.
ABSTRACT: Loggers play critical roles in forest management and resource production, yet supply chain pressures can challenge their economic sustainability. We examine logger perspectives on efficiency, financial challenges, and potential solutions from two contrasting perspectives: 1) business strategy and 2) treadmill of production, a sociological critique of resource production that links economic and ecological sustainability. To provide in-depth perspectives based on lived experiences, we conducted interviews with professional loggers and other stakeholders, focusing on firms with mechanized cut-to-length systems in Wisconsin and Michigan's Upper Peninsula. Our qualitative analysis revealed the intersection of factors that help explain financial stress. Loggers work on contract or buy stumpage from landowners and then sell to mills. Perceived challenges included competition in stumpage markets, relationships to mills that disadvantaged small firms, debt from mechanization, and site access through variable environmental conditions. Loggers worked to increase efficiency and production volume, though some loggers expressed the limits of increasing efficiency and production for improving profitability. Proposed solutions to reduce financial stress included long-term mill contracts, access to loans, and improved financial literacy. Nonetheless, individual firm efficiency will not address structural challenges such as loggers' role in the supply chain between landowners and mills.